2013
DOI: 10.4172/2155-9899.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination: A Target for Disease Intervention in Multiple Sclerosis and other Inflammatory Diseases?

Abstract: Citrullinated histone epitopes are involved in the very early stages of inflammatory responses. An important early event is the activation of neutrophils. It has been shown that Peptidyl Arginine Deiminase (PAD) expression levels increase upon pro-inflammatory signalling followed by activation of neutrophils. Subsequently, PAD enzymes cause histone citrullination in the activated neutrophils. Histone citrullination is involved in various processes. One of the most important is NETosis, which results in the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 83 publications
1
37
0
Order By: Relevance
“…Since PAD activity is highly Ca 2+ dependent, changes in Ca 2+ fluxes induced in cytokine-exposed b-cells might play a role. The present findings, together with the recent report on posttranslationally modified GAD65 (15), add type 1 diabetes to the list of autoimmune diseases involving citrullination, i.e., RA, multiple sclerosis, and systemic erhythematosus (32). This suggests that citrullination is not a specific diseaserelated event but rather an inflammation-dependent process occurring preferentially in autoimmune target tissues.…”
Section: Discussionsupporting
confidence: 66%
“…Since PAD activity is highly Ca 2+ dependent, changes in Ca 2+ fluxes induced in cytokine-exposed b-cells might play a role. The present findings, together with the recent report on posttranslationally modified GAD65 (15), add type 1 diabetes to the list of autoimmune diseases involving citrullination, i.e., RA, multiple sclerosis, and systemic erhythematosus (32). This suggests that citrullination is not a specific diseaserelated event but rather an inflammation-dependent process occurring preferentially in autoimmune target tissues.…”
Section: Discussionsupporting
confidence: 66%
“…51 There is growing evidence of the pathological role of NETs in the development and progression of multiple acute and chronic inflammatory diseases. [5][6][7][8][9]52 First, NETs act as a source of autoantigens that break immunological tolerance in autoimmune diseases, including RA, SLE, APS, and ANCA-associated vasculitis. 53 Second, the cytotoxicity of NETs results in local inflammation that leads to tissue damage, organ failure and severe morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Citrullination of proteins is understood to be an important post-translational modification with systemic implications (Chirivi et al, 2013). Previous studies have shown that up-regulation of peptidyl arginine deiminase (PAD) expression and the associated increase in citrullinated proteins were found in patients with rheumatoid arthritis (Foulquier et al, 2007).…”
Section: Proteome Associated With Microbe-host Interactionmentioning
confidence: 99%